A mathematical model on the suppression of hail growth - SINHA, D. K.; BANERJI, BRATATI; CHAUDHURI , SUTAPA (MAUSAM, 1990)
This paper presents essentially a dynamic model on the suppression of hail growth in mathe matical terms. The interaction between the hygroscopic seeding and microphysical parameters are considered and their effects on the total amount of hail and rainfall available at the surface are investigated. The present model reveals some important charlatanistic features on the control of the growth of a hailstone. Correlations are observed between seeding and embryo radius as well as between seeding and the density of the hailstone. The concentration of ice is found to reduce sufficiently in the seeded case with a possibility of less availability of hail at the surface. The present model is compared with the model developed by the same group of authors (Banerji et al. loc. cit.). It is found that the hygroscopic seeding controls the growth of hailstone.